Reputation and credit without collateral in Africa's formal banking. - Nkurunziza, J (CSAE (University of Oxford), 2005)
The analysis of reputation as a contract enforcement instrument where legal institutions, especially commercial courts, fail to enforce commercial contracts has focused on informal credit markets. The literature centres on the argument that lenders or co-borrowers in group lending can easily monitor each borrower, given the small size of an individual lender's market. Verifiability allows the detection of opportunistic default and hence allows its punishment. This paper argues that in Africa, even formal credit markets rely on reputation. However, the modelling strategy is not based on monitoring and verifiability, given the potential for residual information asymmetry between a bank and a borrower after screening. Instead, the paper conceptualises the relationship between a bank and a borrower as an infinitely repeated game. The bank learns the type of the borrower through repeated interaction, a process by which a borrower builds his reputation as an honest partner. A defaulting dishonest borrower forfeits his access to future loans. The main result of the model is that the higher the reputation of a borrower, the lower his equilibrium payoff that is incentive compatible with debt repayment. Conversely, in the absence of any reputation, the payoff that is incentive compatible with repayment is equal to infinity meaning that credit trade is impossible without either a credible formal contract enforcement mechanism or some level of reputation.